2008
DOI: 10.1016/j.ab.2008.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and analysis of transcription on large, surface-mounted single template DNA molecules

Abstract: A surface-based approach is presented for the transcriptional analyses of large, single DNA molecule templates and their imaged reaction products by RNA polymerase (RNAP). Results showed surfaces with a charge density supporting stretching of single DNA molecules to 70-80% of their full contour length were ideal for analysis of T7 RNAP transcription complexes on bound single template DNAs. Such DNA molecules were shown to sustain efficient transcription reactions and analysis, which enabled localization of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…46 Using the average FWHM to estimate resolution, 46 the extensional-flow stretching method may be able to discriminate between target sequences separated by as little as 2 kb, an improvement over the resolution reported for direct linear analysis (DLA), where DNA are entrained and stretched in a contraction flow. 16,47 For comparison, peak resolutions of 1-5 kb (based on FWHM) have recently been demonstrated [48][49][50] for ensembles of 100-600 slide-immobilized samples. Ultimately, any method based on optical detection for a population of molecules will likely be diffraction limited with a minimum resolution of $0.5 kb for fully extended stained DNA.…”
Section: Resultsmentioning
confidence: 99%
“…46 Using the average FWHM to estimate resolution, 46 the extensional-flow stretching method may be able to discriminate between target sequences separated by as little as 2 kb, an improvement over the resolution reported for direct linear analysis (DLA), where DNA are entrained and stretched in a contraction flow. 16,47 For comparison, peak resolutions of 1-5 kb (based on FWHM) have recently been demonstrated [48][49][50] for ensembles of 100-600 slide-immobilized samples. Ultimately, any method based on optical detection for a population of molecules will likely be diffraction limited with a minimum resolution of $0.5 kb for fully extended stained DNA.…”
Section: Resultsmentioning
confidence: 99%
“…This is comparable to or better than previous single molecule target sequence position determination; for example resolutions of 1–5 kb, based on the full width at half maximum of populations of 100–600 slide-immobilized DNA molecules, have been recently reported by other single molecule techniques. 79 We previously demonstrated the use of cross slot flows for sequence detection using a biotinylated mutant of EcoRI attached to a NeutrAvidin coated fluorescent nanosphere, 21 however in general the creation of such fluorescent probes is expensive, time-consuming, and the biotinylation or labeling reactions may have low efficiency or interfere with the enzymatic activity. We note that in our earlier study, the error was higher and the precision slightly lower than that reported here; we believe the improved precision in target sequence location in the present case is due to the absence of the nanosphere, which leads to lower fluctuations in the length of the DE complex in this stagnation point flow (see Supplementary information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Restriction enzymes are routinely used for DNA modification and manipulation due to their ability to cut or cleave DNA at specific nucleotide sequences known as restriction or recognition sites. They are widely used in molecular biology, recombinant DNA technology, 1 gene mapping techniques [2][3][4][5][6][7][8][9][10] and DNA sequencing. 11,12 In optical restriction mapping, [3][4][5][6][7] for example, genomic length dsDNA is stretched and immobilized on a substrate, digested with a restriction enzyme, stained with a fluorescent dye, and the positions at which the enzyme has cut the DNA are used to identify the locations of the restriction sites.…”
Section: Introductionmentioning
confidence: 99%
“…10,15 Schwartz and his coworkers used trimethylsilane and dimethyldiethoxysilane (DMDES) coated coverslides to render a hydrophobic surface for effective DNA combing. 16,17 Larson's group reported a novel protein assisted DNA immobilization (PADI) on micro-or nanofluidic surfaces, in which restriction enzymes or RNAP was used to anchor DNA molecules with limited surface interactions. 9 Other notable methods involve the use of biotin-streptavidin coupling, neutravidin coated surfaces, polystyrene coated coverslides, aminopropyltriethoxysilane (APTES) coated surface, receding meniscus on micro-structured polydimethylsiloxane (PDMS) substrates, etc., for DNA stretching and immobilization.…”
Section: Introductionmentioning
confidence: 99%